Preparation and properties of hydroxyl‐terminated cationic waterborne polyurethanes for cathodic electrodeposition coatings. Issue 8 (11th January 2019) - He, Xiaoling; Zhang, Xindan; He, Jingwei; Liu, Fang
Abstract: Hydroxyl‐terminated cationic waterborne polyurethanes (HCWPUs) were synthesized using N ‐methyldiethanolamine ( N ‐MDEA) as internal emulsifier and mixed with cross‐linker of nonionic waterborne blocked polyisocyanate (NWBI) to prepare cathodic electrodeposition (CED) coatings. The effects of N ‐MDEA content, NCO/OH molar ratio, neutralization degree, and NWBI content on the performance of HCWPUs emulsion and relevant CED coatings were investigated. The results showed that 7.5 wt.% of N ‐MDEA content, 0.9/1 of NCO/OH molar ratio, and 100% of neutralization degree were the optimal experimental parameter for synthesizing excellent performance HCWPUs. Incorporation of nonionic waterborne blocked isocyanate could significantly promote the hardness, adhesion, and solvent resistance of CED coatings without influencing the emulsion stability and coatings thermostability.